A Highly Transparent Self-Powered Touch Sensor Based on Hierarchical (Micro-Nano) Cu Grid on Polyethylene Terephthalate Composite Electrodes for Smart Wear - Cao, Weiqi; Shaker, Majid; Lei, Wenqian; Yu, Hua (Journal of Materials Engineering and Performance, 2023)
With the expansion of the applications of sensors, requirements such as flexibility, visual transparency, and self-powering have become critical. In this work, firstly we have adopted photoetch and hierarchical (micro-nano) manufacturing techniques to fabricate a micro-scale copper grid on polyethylene terephthalate (PET). This material (Cu grid @PET) exhibits high transmittance (89% at 550 nm, only 2.7% lower than PET substrate) and low electric resistance (6.7 Ω sq−1) compared with other reports. Then, the as-fabricated Cu grid @PET composite electrode, poly-dimethylsiloxane (PDMS), and polymethyl methacrylate (PMMA) were utilized to fabricate a sandwich-like structured transparent self-powered sensor (TSPFS) with high optical transmittance of 85.5-87.5% (450 620 nm). A complete novel control method combining with sensor’s electrical signal test was implemented by Dynamic Mechanical Analyzer (DMA), verifying the simulation response to space of COMSOL. Voltage signals could be also observed when the sensor was touched by fingers without receiving electric energy from external sources. Finally, the paper shows a kind of smart goggles made of the produced transparent device, exhibiting heating, antifogging, and sensing functions.
CRIS-Team Scopus Importer:2023-03-03
Keywords: coating; laser photoetching; smart wear; transparent and flexible electrode; zero-energy sensor

A review of nitrogen-doped carbon materials for lithium-ion battery anodes - Shaker, Majid; Ghazvini, Ali Asghar Sadeghi; Shahalizade, Taieb; Gaho, Mehran Ali; Mumtaz, Asim; Javanmardi, Shayan; Riahifar, Reza; Meng, Xiao min; Jin, Zhan; Ge, Qi (New Carbon Materials, 2023)
One of the most important research areas related to Li-ion batteries is the replacement of the graphite anode with other carbon materials such as hard carbons, activated carbons, carbon nanotubes, graphene, porous carbons, and carbon fibers. Although such materials have shown better electrochemical performance for lithium storage compared to graphite, there is plenty of room for improvement. One of the most effective approaches is to dope heteroatoms (e. g. nitrogen) in the structure of the carbon materials to improve their electrochemical performance when they are used as anode materials. We first describe how N-doping has a positive effect on lithium storage and then provide numerous selected examples of this approach being applied to various carbon materials. The characterization of N doped in the structure of different carbon materials by X-ray photoelectron spectroscopy and scanning tunneling microscopy is then presented since they are able to characterize the N in these structures with a high (atomic) resolution. Finally, a statistical analysis is performed to show how the amount of doped N affects the specific capacity of the N-doped carbon materials.
CRIS-Team Scopus Importer:2023-04-28
Keywords: Carbon nanotubes; Graphene; Hard carbon; Lithium-ion battery; Nitrogen doping; Porous carbon

A review on the role of graphene quantum dots and carbon quantum dots in secondary-ion battery electrodes - Shaker, Majid; Shahalizade, Taieb; Mumtaz, Asim; Hemmati Saznaghi, Maryam; Javanmardi, Shayan; Gaho, Mehran Ali; Cao, Weiqi; Hu, Wei; Jin, Zhan; Ge, Qi; Ghazvini, Ali Asghar Sadeghi (FlatChem, 2023)
Developing advanced electrode materials is currently crucial for elevating the capacity and energy density of secondary-ion batteries. Among the plenty of candidates, quantum dots (QDs), especially carbon dots (CDs) and graphene quantum dots (GQDs) have shown promising results to achieve this aim. CDs and GQDs are able to solely or in combination with other electrode materials, provide excellent electrochemical properties. Regarding the literature, the addition of these carbonaceous QDs to the electrode materials and fabricating composite electrode materials is able to remarkably enhance the capacity of the probing devices. Therefore, in this review, firstly an introduction to the role of CDs and GQDs in secondary-ion batteries is given. Then, the application of these QDs is reviewed in lithium-, sodium-, potassium-, aluminum-, and zinc-ion batteries as well as lithium-sulfur batteries. Finally, a conclusion is indited and the outlook of this topic is described.
CRIS-Team Scopus Importer:2023-06-09
Keywords: Carbon dots; Electrochemical performance; Graphene quantum dots; Secondary-ion battery

A scalable dual activation strategy to construct heteroatom-doped graphene-reinforced porous carbon with tunable pores for supercapacitors - Li, Hongjie; Li, Yanyu; Shen, Huyan; Shaker, Majid; Zada, Imran; Zhu, Shenmin; Li, Yao (Journal of Power Sources, 2025)
The development of scalable synthesis methods for heteroatom-doped carbon with tailored pore structures remains a significant challenge. In this study, we present a dual-activation strategy employing KOH and K3PO4 to fabricate heteroatom-doped graphene-reinforced porous carbon with tunable pores (1–4 nm) through electrostatic self-assembly of chitosan and graphene oxide. The optimized material demonstrates a large specific surface area (2672.39 m2 g−1) with dominant (1–4 nm) pores (V(1-4) nm = 1.23 cm3 g−1, V(1-4) nm/Vt = 77.36 %) and favorable heteroatom configurations. Electrochemical tests in a three-electrode system demonstrated exceptional performance, including a specific capacitance of 371 F g−1 at 0.5 A g−1, excellent rate capability (266 F g−1 at 100 A g−1), and remarkable cycling stability (98.2 % retention after 50,000 cycles) in 6 M KOH. Symmetric supercapacitors deliver an energy density of 38.9 Wh kg−1 in 1 M TEABF4/AN electrolyte while maintaining 98.5 % capacity retention over 20,000 cycles in 6 M KOH. This study provides novel insights for designing carbon materials with synergistic pore structure and heteroatom engineering for advanced energy storage.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Dual-activation; Graphene-reinforced; Heteroatom-doped; Supercapacitors; Tunable pores

Carbon/graphene quantum dots as electrolyte additives for batteries and supercapacitors: A review - Shaker, Majid; Ng, Siow Woon; Sadeghi Ghazvini, Ali Asghar; Javanmardi, Shayan; Gaho, Mehran Ali; Jin, Zhan; Ge, Qi (Journal of Energy Storage, 2024)
Electrolyte is a crucial component in electrochemical energy storage devices (EESDs) such as rechargeable batteries and supercapacitors (SCs). While a substantial effort has been directed to engineering the electrodes, fewer but effective and continuous efforts have been devoted to improve the devices' performance through the modification of their electrolytes. Among these approaches, the strategic integration of minor amounts of additives has led to the formation of appropriate solid-electrolyte interphase (SEI) and cathode-electrolyte interphase (CEI), as well as modifying the ionic conductivity, preventing dendrite growth, and improving charge storage kinetics. Among various additives in the electrolytes, carbon quantum dots (CDs) and graphene quantum dots (GQDs) have emerged as favorable options due to their positive influence on the electrolytes for EESDs. These QDs are soluble in specific solvents and their numerous functional moieties allow them to act as electrolyte additives and polyanions. Furthermore, their excellent physiochemical properties make them excellent candidates as fillers in solid-state electrolytes. The excellence of these QDs is verified by numerous electrochemical and physiochemical characterization methods affirming their positive influence on various parameters such as ion-diffusion kinetics, capacity, and resistance. The application of CDs and GQDs in the electrolytes of EESDs is new and the ruling mechanisms are not well-known yet. This review article provides an overview of the application of CDs and GQDs in both liquid and solid electrolytes for lithium-, sodium-, potassium-, zinc-ion and lithium metal batteries besides SCs. Herein, we aim to offer valuable insights into designing and fabricating a new class of electrolyte additives based on CDs and GQDs for realizing novel electrolytes for EESDs.
CRIS-Team Scopus Importer:2024-03-15
Keywords: Battery; Carbon dots; Electrolyte additives; Graphene quantum dots; Supercapacitor

Coverage- and temperature-induced self-metalation of tetraphenyltransdibenzoporphyrin on Cu(111) - Shaker, Majid; Muth, Maximilian; Steffen, Julien; Ceccatto Dos Santos, Alisson; Jaekel, Simon; Adhikari, Rajan; Gazetas, Pascal; Oleszak, Christoph; de Siervo, Abner; Jux, Norbert; Görling, Andreas; Lytken, Ole; et al. (Journal of Physics: Condensed Matter, 2025)
We have investigated the adsorption and self-metalation of free-base tetraphenyltransdibenzoporphyrin (2H-TPtdBP) on Cu(111) as a function of coverage and temperature using scanning tunneling microscopy, x-ray photoelectron spectroscopy, temperature programmed desorption, and density-functional theory calculations. At low coverages (<0.16 molecules nm-2), we observe isolated individual molecules with an inverted conformation and no self-metalation up to 363 K. At higher coverages, both the formation of ordered islands and self-metalation are observed over time already at room temperature, and accelerate upon heating to 363 K. At 423 K, complete self-metalation occurs for all coverages up to the completed first layer. By comparing our results for 2H-TPtdBP to the existing literature on other tetraphenyl-based porphyrins, we demonstrate how adsorption and self-metalation can be tailored by the choice of substituents.
CRIS-Team Scopus Importer:2025-02-04
Keywords: DFT; porphyrins; self-assembly; self-metalation; STM; TPD; XPS

Large-scale fabrication of graphene/polyamide-6 composite as a high thermal conductivity engineering composite for thermal radiators - Cao, Weiqi; Shaker, Majid; Meng, Xiaomin; Feng, Huan (Materials Letters, 2022)
In this study, graphene was mass-produced from graphite through ultrasonic-assisted exfoliation in N-methyl-2-pyrrooxone (NMP) and then mixed with polyamides Nylon (PA6) to obtain a high thermal conductivity engineering polymer (GP6). The thermal conductivity of GP6 is 30 W m−1 K−1 and the density is 1.8 g cm−1. GP6 could be used in heat dissipation systems of LED lamps and cameras with injection molding at 260 °C, thus cutting the cost by 30% and reducing the carbon emission.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Exfoliation; Graphene; Polymeric composites; Thermal properties

On the adsorption of different tetranaphthylporphyrins on Cu(111) and Ag(111) - Brox, Jan; Adhikari, Rajan; Shaker, Majid; Ruppel, Michael; Jux, Norbert; Marbach, Hubertus; Jaekel, Simon; Steinrück, Hans-Peter (Surface Science, 2022)
We address the adsorption of 2H-tetranaphthylporphyrin (2HTNP) and 2H-tetranaphthylbenzoporphyrin (2HTNBP) on Cu(111) and Ag(111). The difference between the two molecules is that for 2HTNBP the pyrrole groups are replaced by isoindole groups. We were interested in the resulting differences in the adsorption behavior on the two surfaces, in particular the role of the naphthyl groups. The investigations are performed with scanning tunneling microscopy at room temperature (RT) and after heating treatments (500 and 600 K). On Ag(111), 2HTNP forms a commensurable superstructure at RT, which transforms to a denser packed, non-commensurable structure upon annealing. For 2HTNBP, individual molecules are observed on Cu(111) at RT, which exhibit different mobility. In contrast, on Ag(111) the formation of ordered 2HTNBP islands occurs, which are stabilized by T-type interactions. After heating to 500 K, these islands undergo a structural change to a denser packed structure, which is stabilized by π-π stacking of neighboring naphthyl groups.
CRIS-Team Scopus Importer:2022-04-01
Keywords: Commensurability; Naphthyl functionalization; Porphyrins; Self-assembly; STM

Prediction of the lithium storage capacity of hollow carbon nano-spheres based on their size and morphology - Shaker, Majid; Yaghmaee, Maziar Sahba; Shahalizade, Taieb; Ghazvini, Ali Asghar Sadeghi; Riahifar, Reza; Raissi, Babak; Ge, Qi (Journal of Materials Science: Materials in Electronics, 2022)
To date, there is an enormous experimental research focus on discovering the usage of carbon materials as Lithium-ion battery (LIB) anode active materials, though there is a limited number of scientific articles exploring the links between the properties of these materials and their lithium storage performance. The goal of this study is to find the relationship between the size and shape of carbon hollow spheres and their lithium storage capacity via modeling. This research considers the lithium storage of hollow carbon spheres originated from two distinct bulk- and surface-dependent mechanisms. Based on this assumption, a unique model is developed that uses a factor termed “normalized volume” to appropriately consider and estimate the contribution of the surface and bulk phenomena to the lithium storage capacity of a carbon hollow sphere. The model exhibited that shrinking the shell thickness of carbon hollow spheres to less than 20 nm significantly increases their lithium storage capacity. The agreement of the predicted and experimentally reported lithium storage capacities was evaluated by comparing the calculated values to experimental data from the literature. This model has the potential to be used as a foundational method or guideline to forecast the lithium storage capacity of different nano-scaled carbon materials regarding their inner structure, size, and shape.
CRIS-Team Scopus Importer:2022-05-13